Aqad al-'amal al-qanuni taht al-aikhtibar bayn al-qanuni al-Umanii wa-al-Misrii - AlKhatib, Tammam Safwan; الخطيب, تمّام صفوان (Universiti Sains Islam Malaysia, 2024)
3170004 - Faculty of Syariah and Law, Universiti Sains Islam Malaysia